The world at war - Thames Television, ltd.; Imperial War Museum (Great Britain).; A & E Home Video (Firm).; New Video Group (New York A & E Home Video ; Distributed by New Video, 1973)
"An extraordinary collection of newsreel, propaganda, and home-movie footage drawn from the archives of 18 nations, including color close-ups of Adolf Hitler taken by his mistress, that present an unvarnished perspective of the war's pivotal events. Penetrating interviews with eyewitness participants - from Hitler's secretary to Alger Hiss to ordinary citizens who stood outside the battle lines - and spine-tingling, first-hand accounts to an already unforgettable experience."--Container.
v. 1 New Germany 1933-39 / directed by Hugh Ragget ; written by Neal Ascherson ; Distant war : September 1939-May 1940 / directed by David Elstein ; written by Laurence Thompson ; France falls : May-June 1940 / written & produced by Peter Batty ; The world at war : the making of the series / Thames Television ; director, Peter Tiffin (ca. 48 min. ; 1989) -- v. 2. Alone : May 1940-May 1941 / produced & directed by David Elstein ; written by Laurence Thompson ; Barbarossa : June-December 1941 / written & produced by Peter Batty ; Banzai! : Japan 1931-1942 / written & produced by Peter Batty ; On our way : U.S.A. 1939-1942 / written & produced by Peter Batty -- v. 3. Desert : North Africa 1940-1943 / written & produced by Peter Batty ; Stalingrad : June 1942-February 1943 / directed by Hugh Ragget ; written by Jerome Kuehl ; Wolf pack : U-boats in the Atlantic 1939-1944 / produced & directed by Ted Childs ; written by J.P.W. Mallalieu ; Red star : the Soviet Union 1941-1943 / produced & directed by Martin Smith ; written by Neal Ascherson -- v. 4. Whirlwind : bombing Germany September 1939-April 1944 / produced & directed by Ted Childs ; written by Charles Douglas Home ; Tough old gut : Italy November 1942-June 1944 / produced by Ben Shephard ; written by David Wheeler ; It's a lovely day tomorrow : Burma 1942-1944 / produced & directed by John Pett ; written by John Williams Home fires : Britain 1940-1944 / produced by Phillip Whitehead ; written by Angus Calder -- v. 5. Inside the Reich : Germany 1940-44 / produced by Phillip Whitehead ; written by Neal Ascherson ; Morning : June-August 1944 / produced & directed by John Pett ; written by John Williams ; Occupation : Holland 1940-1944 / produced & directed by Michael Darlow ; written by Charles Bloomberg ; Pincers : August 1944-March 1945 / written & produced by Peter Batty -- v. 6. Genocide : 1941-1945 / produced & directed by Michael Darlow ; written by Charles Bloomberg ; Nemesis : Germany February-May 1945 / produced & directed by Martin Smith ; written by Stuart Hood ; Japan : 1941-45 / directed by Hugh Ragget ; written by Courtney Browne ; Pacific : February 1942-July 1945 / produced & directed by John Pett ; written by David Wheeler -- v. 7. Bomb : February-September 1945 / written & produced by David Elstein ; Reckoning : 1945...and after / written & produced by Jerome Kuehl ; Remember / written & produced by Jeremy Issacs -- v. 8. Bonus documentaries : Hitler's Germany : the people's community 1933-1939 / written by Jerome Kuehl ; produced by Raye Farr (ca. 74 min. ; 1976) ; Hitler's Germany : total war 1939-1945 / written by Jerome Kuehl ; produced by Raye Farr (ca. 76 min. ; 1976) ; y The two deaths of Adolf Hitler / produced & directed by Martin Smith (ca. 46 min. ; 1975) -- v. 9. Secretary to Hitler / written & directed by Michael Darlow (ca. 23 min. ; 1974) ; Warrior / produced by Alan Afriat ; (ca. 49 min. ; 1975) ; From war to peace / produced by Jerome Kuehl (ca. 23 min. ; 1975?) -- v. 10. Final solution, pt.1 / written & directed by Michael Darlow (ca. 95 min. ; 1975) Final solution, pt. 2 / written & directed by Michael Darlow (ca. 89 min. ; 1975) -- v. 11. Making the series (a 30th anniversary retrospective) (ca. 123 min. ; 2004?) ; Experiences of war (ca. 58 min. ; 2004?) ; special features.
Bonus documentaries have note: "The world at war : a special presentation"
Special features: disc 1: The making of the series; disc 11: The history of 'The world at war'; biographies; gallery of photos from the Imperial War Museum collection. Discs 8-11 contain bonus documentaries, compiled from interviews and archive materials gathered for the series World at war.
Originally broadcast in 1974; bonus documentaries produced between 1974-2004.
Narrator, Laurence Olivier ; music, Carl Davis ; editor, Alan Afriat ... [et al.] ; narrator (v. 8 & 10), Eric Porter.
Interviews with: Traudl Junge, Mitsuo Fuchida, Alger Hiss.
DVD videos.
Keywords: World War, 1939-1945 -- Campaigns -- France; World War, 1939-1945 -- Campaigns -- Great Britain; World War, 1939-1945 -- Campaigns -- Pacific Ocean; World War, 1939-1945 -- Campaigns -- Africa, North; Pearl Harbor (Hawaii), Attack on, 1941.; Stalingrad, Battle of, Volgograd, Russia, 1942-1943.; Genocide; Germany -- History -- 1933-1945.; Japan -- History -- 1926-1945.; Hiroshima-shi (Japan) -- History -- Bombardment, 1945.